From ethical review to responsible research and innovation - e uthor; Reber, Bernard (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2016)
Annotation The concept of RRI has emerged as a new framework to be used by the European Commission for research projects. It now lies at the core of the Horizon 2020 programme and is designed to replace current assessment practices focused on ethical review. The book analyses the shift from ethical review to RRI: what remains of the former, what has been gained? It then makes a critical presentation of existing ethical reviews from the perspectives of moral philosophy and the philosophy of technology and discusses conceptions of ethical assessment on different levels.
Research Ethics Expertise -- Responsible Research and Innovation: a Composite and Ambitious Notion -- Responsibility: A Polysemous Concept -- Responsibility in Innovation and Research: The Need for Moral Innovation -- Governance Devices and RRI Put to the Test -- Conclusion: From Ethics to Responsibility and Back Again.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed July 6, 2016).
John Wiley and Sons
Keywords: Research -- Moral and ethical aspects; Recherche -- Aspect moral; BUSINESS & ECONOMICS -- Business Ethics; Research -- Moral and ethical aspects